The paternal function: conceptual and therapeutic relevance - Davies, Nicholas Charles Christopher (My University, 2016)
: The construct of the ‘pre-oedipal’ paternal function, as distinct from the traditional ‘oedipal’ paternal function, is an important yet under-developed focus of study in both the field of infant development and psychoanalytic clinical practice. This thesis contributes towards the development of an integrated concept of the paternal function as well as to a deeper understanding of the different aspects of the construct and its application. A critical literature review of psychoanalytic literature on the ‘paternal function’ highlights an absence of recognition of the importance of the construct, as it is salient in the earliest period of infancy, and characterises it as fragmented and diversely understood when it is mentioned. Four aspects of the paternal function which appear to be the dominant aspects in the literature are identified and elaborated in some detail. Also noted is the tendency for the non-gendered nature of several aspects of the paternal function to be overlooked because of the regular conflation of the role of the father and the paternal function. Extending this theoretically based observation into the domain of therapeutic practice, the conceptualisations of the pre-oedipal paternal function and the extent to which it is employed as a clinical tool was garnered from a sample of self-identified psychoanalytic psychotherapists based in Johannesburg, South Africa. Interviews of the topic were conducted with eight experienced practitioners and subject to thematic analysis guided by existing theory. The findings articulated closely with the international literature which points to a nebulous understanding of the concept and a general absence of reference to it as relevant in clinical formulations. In addition, based on the interview data, some proposals as to why the paternal function poses such a definitional difficulty and why, furthermore, the paternal functionary is apparently persona non grata in the clinical setting, are discussed. Finally, the case for the usefulness of the pre-oedipal paternal function in clinical practice is elucidated through the discussion of four clinical cases, each addressing a particular aspect of the pre-oedipal paternal function. Based on both a critical review of the literature and empirical data in the form of interviews of psychotherapists, and case material, the thesis makes a cogent case for foregrounding and refining conceptual and applied understandings of the construct of the ‘pre-oedipal’ paternal function, highlighting the gendered and non gendered attributes associated with performance of a set of functions associated with the construct.
Keywords: Paternal function; Role of the father; Thirdness; Masculinity; Pre-oedipal